THE ROLE OF EDUCATION IN MODERNIZING CROATIA IN THE 2ND HALF OF THE 19TH CENTURY - Iveljić, Iskra (2011)
THE ARTICLE DEALS WITH THE MODERNIZATION OF SCHOOL SYSTEM IN CROATIA AND THE ROLE OF EDUCATION IN THE SOCIAL, POLITICAL AND CULTURAL CONTEXT
Projekt MZOS
ENG